Pengaruh Service Marketing Mix terhadap Keputusan Nasabah untuk Menabung Pada PT. Bank Mayapada Internasional TBK Cabang A.Yani Pekanbaru - Evelyn Wijaya; Puspa Marantika Ariyani (COSTING : Journal of Economic, Business and Accounting, 2018)
Right now the amount of bank in Indonesia has reached 115 bank (OJK). Increasing number of bank has impact to increasing level of competition. Marketing becomes one of important activity in the company to keep the company existency to develop and get a profit. This research aims to test the influence of service marketing mix (product, price, place, promotion, process, people and physical evidence) on customer saving decision at PT Bank Mayapada International Tbk Cabang A.Yani Pekanbaru. The sample used are 100 respodents by using accidental sampling method. The data analyzed using multiple linear regression. The result showed that product, place, process and person has a significant effect on customer saving decision whereas price, promotion and physical evidence has no significant effect to customer saving decision at PT Bank Mayapada International Tbk Cabang A.Yani Pekanbaru. Keywords: Product, Price, Place, Promotion, Process, Person, Physical Evidence and Customer Saving Decision.